The Effect Of Competitive Style And Peer Teaching On Knowledge Acquisition Achievement Of Some Methods Of Teaching Concepts - Kareem, Amena (Journal of Physical Education, 2017)
The aim of the research is to identify the effect of competitive – comparative style and peer teaching in knowledge acquisition in methods of teaching as well as finding the differences between the groups of the research. The researcher used the experimental method. The subjects were (151) sophomore students from physical education and sport sciences college/ Kurkok University 2016 – 2017. The subjects were taken from three sections ; A, B, C in which sections A and B formed the two experimental groups the first one followed competitive – comparative style while the second followed peer teaching styles. A special teaching program was designed for some methods of teaching concepts. The program lasted for 8 weeks with one teaching session per week for each style. The program started from 15/11/2016 till 10/1/2017. The data was collected and treated using proper statistical operations. The researcher concluded that both competitive - comparative style and peer teaching have a positive effect on knowledge acquisition of some methods of teaching concepts. The second group that studies peer teaching style surpassed the first group that studies competitive – comparative style of some methods of teaching concepts. The researcher recommended using peer teaching in methods of teaching in sophomore students of physical education and sport Sciences College due to its great effect on learning the concepts. Finally the necessity of making training courses for training using peer teaching style as well as the necessity of making similar studies on other theoretical science